Analisis Kesalahan Berbahasa Tataran Morfologi dan Sintaksis dalam Penulisan Berita di Media Massa Online KabarPendidikan.id - Salfa Astiara Nadhifa; Prima Gusti Yanti (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this research is to describe and analyze error based on morfology and syntax rules in writing news article on online media KabarPendidikan.id. Research method uses qualitative descriptiv e approach on using technique Studying Document and Writing Note. Research data which is used for the research, are several news that have some mistakes or errors on writing based on morphology and syntax rules. Data references are derrived from 16 news on KabarPendidikan.id online news media in 4 months period from June - September 2022 with using only 4 news articles from each month. Based on Result of the Research, researcher found several mistakes on writing based on morphology and syntax rules on 16 news articles which mistake on morphology consist errors including (1) Improper Determination of Base Forms, (2) Omission of Affixes, (3) Improper Use of Affixes, (4) Omission of Prefix meng-, (5) Omission of Prefix ber-, and (6) Formation of Words with Confixes di -...- kan. For Syntax errors consist (1) Illogical Sentences, (2) Use of Excessive or Redundant Elements, (3) Unpredicated Sentences, (4) Improper Wording, (5) Double Plundering, (6) Ambiguous Sentences, (7) Omission of Conjunctions, (8) Sentences without a Subject, (9) Orders that are Not Parallel, and (10) Use of Foreign Terms.